Hubungan Tingkat Activity Daily Living dengan Tingkat Depresi pada Pasien Stroke di RSUD Prof Dr Margono Soekarjo Purwokerto - Diyan Pangestu, Uti; Riyaningrum, Wahyu (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Stroke is the largest cause of disability worldwide and is second to heart disease. Problems often faced by stroke patients include the inability to perform activity daily living (ADL) due to decreased motor function. This inability causes many stroke patients to experience depression. Knowing the relationship between the level of activity daily living with the level of depression in stroke patients at Prof. Dr. Margono Soekarjo Purwokerto Hospital. This study is an observational quantitative study, with a cross sectional approach. The sample used in the study was stroke patients who did inpatient Adenium Prof Dr Margono Soekarjo Purwokerto Hospital as many as 48 respondents who were taken using nonprobability sampling technique. Data collection was done using a questionnaire, then processed and analyzed using Fisher's Exact Test. The average age of respondents is 56-65 years or the late elderly category, the gender of most respondents was female (58.3%). The education level of most respondents is elementary education (43.8), while the most dominant disease history is respondents who have a history of disease (60.4%). The ADL level of stroke patients in the Adenium room of Prof. Dr. Margono Soekardjo Purwokerto Hospital was mostly in the severe category (52.1%). The level of depression in stroke patients in the Adenium room of Prof. Dr. Margono Soekardjo Purwokerto Hospital mostly had depression in the mild category (45.8%). There is a relationship between the level of ADL with depression in stroke patients in the Adenium room of Prof. Dr. Margono Soekarjo Purwokerto Hospital.